2022
DOI: 10.3390/children9111619
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Adipokines and Incretins in Adolescent Idiopathic Scoliosis: A Pilot Study

Abstract: Adolescent idiopathic scoliosis (AIS) is a three-dimensional malformation of the spine of unknown cause that develops between 10 and 18 years old and affects 2–3% of adolescents, mostly girls. It has been reported that girls with AIS have a taller stature, lower body mass index (BMI), and bone mineral density (BMD) than their peers, but the causes remain unexplained. Energy metabolism discrepancies, including alterations in adipokine and incretin circulatory levels, could influence these parameters and contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…In mice, the high production of hepatic serum amyloid A1 promoted chronic inflammation and caused bone loss [ 97 ]. Regarding cofilin-1, a recent pilot study reported adipokines were implicated also in AIS development and progression [ 98 ]. Bisphosphonates disrupts actin organization and decreases in vitro cofilin levels, an actin regulatory protein that severs actin filaments [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the high production of hepatic serum amyloid A1 promoted chronic inflammation and caused bone loss [ 97 ]. Regarding cofilin-1, a recent pilot study reported adipokines were implicated also in AIS development and progression [ 98 ]. Bisphosphonates disrupts actin organization and decreases in vitro cofilin levels, an actin regulatory protein that severs actin filaments [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance in the lipid profile has also been suggested as a marker of AIS [15]. In addition, the literature data indicate that abnormal levels of many hormones, including estrogen, melatonin, growth hormone, leptin, adiponectin, calmodulin, and ghrelin, may be related to the development and progression of AIS [10,[16][17][18][19][20]. Furthermore, recently published studies have highlighted body composition as an essential factor in the onset and development of AIS [21,22].…”
Section: Introductionmentioning
confidence: 99%